2012
DOI: 10.1111/j.1445-2197.2012.06234.x
|View full text |Cite
|
Sign up to set email alerts
|

Gallstones in New Zealand: composition, risk factors and ethnic differences

Abstract: This novel prospective study highlights risk factors and ethnic differences in gallstone composition in New Zealand. These may be important when considering gallstone prevention strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 28 publications
0
17
0
Order By: Relevance
“…These rates are further summarized in Figure 2. Gallbladder cancer as a consequence of long-standing gallstones is also over-represented among New Zealand Maori,17 suggesting an increased prevalence of gallstones in this native population 18. Ethnic predilections exist in the USA, where Caucasians carry a higher prevalence of gallstones (16.6% of women and 8.6% of men) compared with Black Americans (13.9% of women and 5.3% of men) 14,19…”
Section: Risk Factorsmentioning
confidence: 99%
“…These rates are further summarized in Figure 2. Gallbladder cancer as a consequence of long-standing gallstones is also over-represented among New Zealand Maori,17 suggesting an increased prevalence of gallstones in this native population 18. Ethnic predilections exist in the USA, where Caucasians carry a higher prevalence of gallstones (16.6% of women and 8.6% of men) compared with Black Americans (13.9% of women and 5.3% of men) 14,19…”
Section: Risk Factorsmentioning
confidence: 99%
“…Cholecystectomy is among the top 10 surgical procedures performed each year in Western societies; 2 with more than 500 000 patients are performed annually in the United States, consuming resources estimated at $6.5 billion (Stringer et al, 2013). In the present study, we demonstrated that gallbladders excised from patients with symptomatic cholelithiasis, even without any evidence of inflammation, might host bacteria in over 20% of cases (Gosling et al,1996).…”
Section: Author(s) Agree That This Article Remains Permanently Open Amentioning
confidence: 48%
“…Gallstone disease is a common and costly disorder worldwide; it is often asymptomatic, biliary colic, cholecystitis and entails life-threatening complications such as obstructive jaundice (Stringer et al, 2013). The pathophysiological role of bacteria in the formation of gallstones was proposed long ago.…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of the most frequent type of gallstone remained a controversy in the literature. With a prevalence ranging from 36.8 to 53.0% some authors [46] reported pure cholesterol gallstone as the predominant type; authors [7–12] reporting a prevalence of pigment gallstone of 37.2% −35% sustained the predominance of this type; elsewhere in the literature, mixed gallstone (66.7% - 89.14%) was reported to be predominate [13–15].…”
Section: Introductionmentioning
confidence: 99%